H2S inhibits apo(a) expression and secretion through PKCα/FXR and Akt/HNF4α pathways in HepG2 cells. (28th June 2016) - Qu, Kai; Liu, Ya‐mi; He, Xing‐lan; Zhang, Hai; Zhang, Kai; Peng, Juan; Tang, Ya‐ling; Yu, Xiao‐hua; Zeng, Jun‐fa; Lei, Jian‐jun; Wei, Dang‐heng; Wang, Zuo
Abstract: Lipoprotein(a) [Lp(a)] is a strong genetic risk factor for coronary heart diseases. However, the metabolism of this protein remains poorly understood. Efficient and specific drugs that can decrease high plasma levels of Lp(a) have not been developed yet. Hydrogen sulfide (H2 S), a member of the gas transmitter family, performs important biological actions, including protection against cardiovascular diseases and maintenance of the lipid metabolism equilibrium in hepatocytes and adipocytes. In this study, we investigated the possible molecular mechanism of H2 S that influences apolipoprotein(a) [apo(a)] biosynthesis. We also determined the effects of H2 S on apo(a) expression and secretion in HepG2 cells as well as the underlying mechanisms. Results showed that H2 S significantly inhibited the expression and secretion levels of apo(a). These effects were attenuated by the PKCα inhibitor and FXR siRNA. H2 S also reduced HNF4α expression and enhanced FXR expression. The Akt inhibitor partially reversed H2 S‐induced inhibition of apo(a) and HNF4α expression and apo(a) secretion. This study reveals that H2 S suppressed apo(a) expression and secretion via the PKCα‐FXR and PI3K/Akt‐HNF4α pathways.